Forage quality on family farms in Croatia grass silage quality on family farms - Marina Vranić; Mladen Knežević; Goran Perčulija; Josip Leto; Krešimir Bošnjak; Ivana Rupić (Mljekarstvo, 2004)
The aim of the applied research project: “Forage evaluation by NIR spectroscopy” was to monitor the nutritive value of grass silage, corn silage and hay on family farms in Croatia over 6-month feeding (from November 2003 to May 2004) Over last 15 years, grass silage become of the same importance in dairy cows nutrition as other traditionally conserved forage in Croatia. In this paper the nutritive value of grass silage on 19 dairy family farms from 5 counties was investigated. Extension service staff recommended dairy nutrition based on monthly silage analysis by NIRS instrument (Foss, Model 6500). Scottish calibration models were applied and following parameters are estimated: dry matter corrected (DM), crude protein (CP), degradable crude protein (DCP), neutral detergent fiber (NDF), metabolizable energy (ME), pH value, ammonia nitrogen, sugar, digestibility of organic matter in dry matter (D-value) and intake factor by cattle (IF). The results show big variations in the average nutritive values of all the investigated parameters. The biggest variations were observed in DM (from 166-785 g kg-1), CP (60-220 g kg-1DM), NDF (300-605 g kg-1DM) and NH3-N (61-530 g N kg-1 of total N). Statistically significant differences (P<0.05) were observed for DM, NDF, ME, sugar content and D-value.